Opportunistic behaviours of Chinese Olympic champions - Liu, C.; Zheng, H.; Sun, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction China`s elite sports performers has made universally acknowledged achievements. However, controversy and discussion are also extremely intense when triggered by the Olympic gold medal phenomenon, "Liang Jing-jing". The purpose of this paper is to decipher the Olympic Games success and its "gold rush", and to study the incentive-restraint mechanism of Olympic champions. This paper also examines the source of the "gold rush", the main reasons for opportunistic behaviour of the Olympic team following championship success. Solutions to these problems will be explored. Methods This investigation utilised the method of game theory analysis, and the property rights of human capital, to establish two models. The first model assumes there are two parties; the principal, and agents. The principal can be the State Sport General Administration, and agents are the Olympic team. In the game, the principal can choose to trust or not trust agents. If the principal chooses not to trust agents, transactions will not occur, the game ends, and the proceeds of principal and agents are zero units of income. If the principal chooses trust, then agents may choose honesty or deception. If the agents choose honesty, each party will receive six units of income. If agents choose deception, the principal will lose six units of income whilst agents will receive twelve. The Nash equilibrium game result is that the principal generally choose not to trust, and agents choose deception. The second model interprets the source of the differences in the Olympic team`s behaviour after winning championships. Assume that agents` current income is R in the field of A after choosing deception, as long as agents make honest behaviours in the field A. In the subsequent transactions, the probability of return is P1, and the results of subsequent phases of the game is the same. At that time, the proceeds of agents that choose to deceive is 12 + R + R / (1-P1). If 12 + R + R / (1-P1)> 6/1-p, agents choose opportunistic behaviours, deception, rationally. The key to understand the behaviours of agents (the Olympic team) is to understand the variables R and P1 in the model, but these values differ after Olympic success. Before winning, the Olympic team is comprised of pre-successful athletes, it is very difficult to receive a large return (R) in other areas (Field A). However, after victory, the Olympic team consists of champions and has high commercial value. At this point, attaining return R in the field A, is not difficult and then the probability P1 of subsequent transactions in A can also be anticipated. Further, the larger the value of R, the higher P1, and thus the ability of Olympic champions to take opportunistic behaviours increases further. Results The characteristic of property rights of human capital (indivisibility) is the source of the "gold rush". The Olympic team`s human capital property characteristic, in addition to the Olympic Games timing and the difference of area are the main reasons for variation in Olympic team behaviour after winning. Establishment of symmetry, and a dynamic incentive-restraint mechanism, are fundamental measures to solve the problem. Conclusions Considering the macro-economic background of economy transition, and the micro-economic foundation of the differences of the Olympic team after winning championships, a number of recommendations are made. The incentive-restraint system of the Olympic team should be improved; and, a long-term mechanism to reform the sports system should be explored. Further, a suitable model for the development of sports for China`s national conditions will guarantee sustainable development of the nation`s sports industry.